Association of sodium-glucose cotransporter-2 inhibitor use and mortality in patients with endometrial cancer: a retrospective cohort study - Min Wang; Mingxia Ye; Maria Lucero; Wanchun Pan; Xin Wang; Heping Zhang; Ling Zhou; Yuanguang Meng (BMC Cancer)
Abstract Background Endometrial cancer is closely linked to obesity and type 2 diabetes mellitus (T2DM). Sodium-glucose cotransporter-2 inhibitors (SGLT2i), originally developed for diabetes, demonstrate potential anti-cancer properties. This study aims to investigate the association between SGLT2i use and all-cause mortality among patients with endometrial cancer. Methods We conducted a real-world, retrospective cohort study using data from the US TriNetX electronic health record database. Female patients diagnosed with endometrial cancer between 2014 and 2023 were included. Propensity score matching (1:1) balanced baseline characteristics, including demographics, comorbidities, and medication use. The primary outcome was overall survival, analyzed via Kaplan–Meier curves and Cox proportional hazards regression. Results A total of 2,079 matched patient pairs were analyzed (SGLT2i vs. non-SGLT2i). SGLT2i use was significantly associated with lower all-cause mortality (8.21% vs. 20.56%; HR, 0.50; 95% CI, 0.41–0.59; P < 0.0001). Subgroup analyses indicated consistent survival benefits in patients regardless of age and body mass index, and those with heart failure, T2DM, and chronic kidney disease. SGLT2i did not increase risks of serious adverse events, including urinary tract infections, ketoacidosis, sepsis, or acute kidney failure. Conclusions As one of the treatments for T2DM, SGLT2i treatment in patients with endometrial cancer was associated with significantly reduced all-cause mortality, highlighting its potential as an adjunctive therapeutic strategy.